Double or nothing [large type] - Sherwood, Kim, 1989- (Sherwood, Kim, 1989- Double 0 novel., 2023)
James Bond, 007, has been captured, perhaps even killed, by a sinister private military company. His whereabouts unknown. Tech billionaire Sir Bertram Paradise claims he can reverse the climate crisis. But can he really? New MI6 spies Johanna Harwood (003), Joseph Dryden (004), and Sid Bashir (009) must uncover the truth.